Learning the Relevance of Relevance and the Trouble with Truth: Evaluating Explanatory Relevance across Childhood. Issue 4 (8th August 2019) - Johnston, Angie M.; Sheskin, Mark; Keil, Frank C.
ABSTRACT: In four experiments, we investigate how the ability to detect irrelevant explanations develops. In Experiments 1 and 2, 4- to 8-year-olds and adults rated different types of explanations about "what makes cars go" individually, in the absence of a direct contrast. Each explanation was true and relevant (e.g., "Cars have engines that turn gasoline into power"), true and irrelevant (e.g., "Cars have radios that play music"), or a false statement that would be relevant if it were true (e.g., "Cars have rockets that speed them up"). Participants of all ages spontaneously indicated that false explanations were less helpful than relevant explanations. However, there was a developmental shift for irrelevant explanations: 4-year-olds only detected irrelevant explanations that did not involve internal features of cars (e.g., "Cars have parking lots that they park in"). Crucially, this shift between age 4 and 5 cannot be explained by 4-year-olds' lack of knowledge since 4-year-olds correctly indicated that relevant explanations were more helpful than irrelevant feature explanations when given a direct contrast in Experiment 3. These results are further clarified in Experiment 4, in which we provided a different explanatory goal ("where to find cars") and found that even young children have a nuanced understanding of explanatory relevance that is sensitive to differing explanatory goals. Together, these four experiments suggest an early-emerging ability to understand relevance, but a shift between age 4 and 5 in the ability to spontaneously use this understanding when evaluating individual explanations in isolation.